The Impact of Cultural Norms on Sustainable Entrepreneurship Practices in SMEs of Bangladesh - Md Mehedi Hasan Emon; Tahsina Khan (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
The objective of this study is to examine the significant impact of cultural norms on sustainable entrepreneurship initiatives in the context of small and medium-sized firms in Bangladesh's dynamic business environment. Utilizing a rigorous research technique, this study conducts semi-structured interviews with a diverse sample of 40 small and medium-sized enterprise owners, executives, and important stakeholders. Following this, a rigorous thematic analysis is conducted, revealing significant themes and complex patterns present in the collected data. The findings reveal a detailed viewpoint, explaining that cultural norms, including factors such as tendencies towards risk avoidance, complex social networks, and the significant impact of family dynamics on business operations, have both positive and negative effects on sustainable entrepreneurship practices in small and medium-sized enterprises. Furthermore, the identified research highlights the utmost importance of governmental policies and regulatory frameworks as influential factors that shape the dimensions of sustainable entrepreneurship. Based on these findings, the research emphasizes the necessity of adopting a comprehensive and integrated strategy that effectively addresses and overcomes the deeply ingrained obstacles rooted in culture. This approach should also prioritize the establishment of a supportive environment, facilitated by well-informed governmental policies and carefully crafted regulations. The implications of these findings have significant resonance beyond the confines of Bangladesh, extending to other developing countries where cultural norms and government regulations can pose substantial obstacles to the achievement of sustainable entrepreneurship. Future research attempts may benefit from delving deeper into the complex relationship between cultural norms and sustainable entrepreneurship practices across various contextual settings.